2009
DOI: 10.1007/s10653-009-9268-z
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic detoxification potential of aox genes in arsenite-oxidizing bacteria isolated from natural and constructed wetlands in the Republic of Korea

Abstract: Arsenic is subject to microbial interactions, which support a wide range of biogeochemical transformations of elements in natural environments such as wetlands. The arsenic detoxification potential of the bacterial strains was investigated with the arsenite oxidation gene, aox genotype, which were isolated from the natural and constructed wetlands. The isolates were able to grow in the presence of 10 mM of sodium arsenite (As(III) as NaAsO(2)) and 1 mM of D: +glucose. Phylogenetic analysis based on 16S rRNA ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 43 publications
1
28
1
1
Order By: Relevance
“…The aerobic arsenite oxidases involved in such processes are heterodimers consisting of a large subunit with a molybdenum center and a [3Fe-4S] cluster (AroA, AsoA, and AoxB) and a small subunit containing a Rieske-type [2Fe-2S] cluster (AroB, AsoB, and AoxA) (1, 13). The large subunit in these enzymes is similar to that found in other members of the dimethyl sulfoxide (DMSO) reductase family of molybdenum enzymes but is clearly phylogenetically divergent from the respiratory arsenate reductases (ArrA) or other proteins of the DMSO reductase family of molybdenum oxidoreductases, such as the new arsenite reductase described recently for Alkalilimnicola ehrlichii (25,31,40).aox genes have been identified in 25 bacterial and archaeal genera isolated from various arsenic-rich environments, most of which belong to the Alpha-, Beta-, or Gammaproteobacteria phylum (7,10,12,14,23,25,29,32,37). Recent studies based on environmental DNA extracted from soils, sediments, and geothermal mats with different chemical characteristics and various levels of arsenic contamination have suggested that the distribution and the diversity of arsenite-oxidizing microorganisms may be greater than previously suggested (6, 10, 14-16, 18, 28, 29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The aerobic arsenite oxidases involved in such processes are heterodimers consisting of a large subunit with a molybdenum center and a [3Fe-4S] cluster (AroA, AsoA, and AoxB) and a small subunit containing a Rieske-type [2Fe-2S] cluster (AroB, AsoB, and AoxA) (1, 13). The large subunit in these enzymes is similar to that found in other members of the dimethyl sulfoxide (DMSO) reductase family of molybdenum enzymes but is clearly phylogenetically divergent from the respiratory arsenate reductases (ArrA) or other proteins of the DMSO reductase family of molybdenum oxidoreductases, such as the new arsenite reductase described recently for Alkalilimnicola ehrlichii (25,31,40).aox genes have been identified in 25 bacterial and archaeal genera isolated from various arsenic-rich environments, most of which belong to the Alpha-, Beta-, or Gammaproteobacteria phylum (7,10,12,14,23,25,29,32,37). Recent studies based on environmental DNA extracted from soils, sediments, and geothermal mats with different chemical characteristics and various levels of arsenic contamination have suggested that the distribution and the diversity of arsenite-oxidizing microorganisms may be greater than previously suggested (6, 10, 14-16, 18, 28, 29).…”
mentioning
confidence: 99%
“…aox genes have been identified in 25 bacterial and archaeal genera isolated from various arsenic-rich environments, most of which belong to the Alpha-, Beta-, or Gammaproteobacteria phylum (7,10,12,14,23,25,29,32,37). Recent studies based on environmental DNA extracted from soils, sediments, and geothermal mats with different chemical characteristics and various levels of arsenic contamination have suggested that the distribution and the diversity of arsenite-oxidizing microorganisms may be greater than previously suggested (6, 10, 14-16, 18, 28, 29).…”
mentioning
confidence: 99%
“…Both As(III) oxidizers and As(V) reducers in Pseudomonas have been isolated before. P. stutzeri GIST-BDan2 (EF429003) is an As(III)-oxidizing strain isolated from constructed wetlands (Chang et al, 2010). Three arsenate reducers of Pseudomonas were isolated in As-rich groundwater (Liao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Many bacteria are also able to reduce arsenate as a means of detoxification using ArsC, an arsenate reductase that is capable of converting intracellular arsenate into arsenite, which is further transported out of the cell by an energy-dependent efflux process (14-16). Arsenite-oxidizing bacteria (AOB) can oxidize As(III) into As(V) under aerobic or anaerobic conditions (17)(18)(19)(20)(21)(22)(23)(24)(25). Under aerobic conditions, AOB are able to convert As(III) into As(V) by using As(III) as an electron donor and oxygen as an electron acceptor (19-23); under anaerobic conditions, some AOB can convert As(III) into As(V) by using As(III) as an electron donor and nitrate, selenate, or chlorate as an electron acceptor (18,(24)(25)(26)(27).…”
Section: Importancementioning
confidence: 99%
“…Arsenite-oxidizing bacteria (AOB) can oxidize As(III) into As(V) under aerobic or anaerobic conditions (17)(18)(19)(20)(21)(22)(23)(24)(25). Under aerobic conditions, AOB are able to convert As(III) into As(V) by using As(III) as an electron donor and oxygen as an electron acceptor (19)(20)(21)(22)(23); under anaerobic conditions, some AOB can convert As(III) into As(V) by using As(III) as an electron donor and nitrate, selenate, or chlorate as an electron acceptor (18,(24)(25)(26)(27). AOB are either chemoautotrophic, using carbon dioxide as the sole carbon source, or heterotrophic, using organic carbon as the sole carbon source.…”
mentioning
confidence: 99%